A134 RATES OF PARENTERAL NUTRITION-ASSOCIATED CHOLESTASIS/LIVER DISEASE AND GROWTH PRE- AND POST-SMOFLIPID INTRODUCTION IN NEONATES AND INFANTS WITH INTESTINAL FAILURE. (26th February 2020) - Tyminski, N; Hudson, A; Turner, J; Silverman, J
Abstract: Background: Parenteral nutrition (PN) is essential for survival in infants with intestinal failure (IF). PN-associated cholestasis (PNAC) and liver disease (PNALD) are life-threatening complications of long-term PN use. SMOFlipid (soybean oil, medium-chain triglycerides, olive oil, and fish oil) has recently been approved as an off-label alternative to the conventional soy-based lipid emulsion (Intralipid). It is thought to have anti-cholestatic properties due to its more diverse lipid composition. Due to its' recent approval in Canada (2013) and the USA (2016), data remains sparse. Aims: We aim to determine if infants with IF receiving SMOFlipid had significantly lower rates of PNAC and improved growth compared to those receiving Intralipid. Methods: All patients (≤1 year old at start of PN therapy) who received PN of any duration at two tertiary pediatric hospitals in Edmonton (2010–2018) were identified from the shared pharmacy database. Those with IF who received one type of PN continuously for ≥6 weeks total were included. Individuals with an initial serum conjugated bilirubin >50 µmol/L and/or who had PN interruptions >5 days were excluded. Data on liver parameters, growth, and complications were collected. Non-parametric tests (Mann-Whitney U test for continuous variables and χ2 test for categorical variables) were used to compare PNAC/PNALD (serum conjugated bilirubin >34umol/L during PN) and growth (weight/length/head circumference z-scores) between SMOFlipid and Intralipid. Results: 1777 patients were reviewed; 40 infants (55% male), median age 4 weeks (range 0–48 weeks) at the time of PN initiation, met the inclusion criteria. Reasons for exclusion (n=1737) were receiving PN <6 weeks total (n=1485), duplicate patients (n=154), receiving multiple types of PN with each less than 6 weeks total (n=62), an initial serum conjugated bilirubin >50umol/L (n=21), more than 5 consecutive days off of PN (n=12), and older than 1 year old at time of PN initiation (n=3). Twenty-one patients (53%) received SMOFlipid, 15 (38%) Intralipid, and 4 (10%) Omegaven for ≥6 weeks. The majority (92%) were in an intensive care unit (neonatal or pediatric). No patients were septic when starting PN. Individuals received PN over a median of 7.9 weeks (range 6–27 weeks). Conclusions: As expected, neonatal onset intestinal failure is rare in Edmonton. In our tertiary pediatric institutions, 2010–2018, SMOFLipid was the predominant lipid choice for infants with intestinal failure, followed by Intralipid. Omegaven was used rarely. This dataset will now allow us to compare the rates of PNAC at six weeks post-PN initiation and differences in growth between infants with IF receiving SMOFlipid versus the traditional Intralipid in our Canadian setting. Analysis is currently underway. Funding Agencies: Women and Children's Health Research Institute (WCHRI) at the University of Alberta